Introducing methoxy or fluorine substitutions on the conjugated side chain to reduce the voltage loss of organic solar cells. Issue 34 (4th August 2021) - Chen, You; Jiang, Chuanxiu; Wang, Jiacheng; Tang, Ailing; Zhang, Bao; Liu, Xinfeng; Chen, Xingguo; Wei, Zhixiang; Zhou, Erjun
Abstract : Herein, three benzotriazole (BTA)-based polymers and a fused benzotriazole-based small molecule were constructed to realize a relatively high power conversion efficiency (PCE) of above 11% with a high open-circuit voltage ( V OC ) approaching 0.99 V. Abstract : Developing an effective method to decrease the voltage loss ( V loss ) and increase the short-circuit current density ( J SC ) simultaneously is of vital importance to realize high-efficiency organic photovoltaics (OPVs). Herein, we adopted three material combinations based on three medium bandgap (1.91 eV) benzotriazole (BTA)-based polymer donors (J52, J52-F, J52-OMe) and a narrow bandgap (1.48 eV) thiophene-fused benzotriazole containing a small molecule acceptor (JC2) to balance the J SC and open-circuit voltage ( V OC ). JC2 extended the light harvesting region, affording a high J SC . Methoxy or fluorine substitutions effectively decrease Δ V 2 and Δ V 3 due to their decreased charge transfer (CT) state absorption and enhanced EL external quantum efficiency (EQEEL ). Consequently, a significant reduction of total voltage loss of 0.589 V is realized in both J52-OMe and J52-F based devices compared to a large one (0.725 V) for J52:JC2. J52-F and J52-OMe achieved high V OC values of 0.991 V and 0.986 V, much higher than that of the J52:JC2 combination (0.850 V). On the other hand, in the substituted two blend films a slower charge transfer process and lower hole/electron mobilities than those of the J52:JC2 blend occurred, leading to their slightly lower J SC . Finally, J52-F:JC2 and J52-OMe:JC2 reach a fine balance between V OC and J SC, producing power conversion efficiencies (PCEs) of 11.4% and 11.2%, respectively. This work not only expands the accessible material combinations used in high V OC systems, but also provides a deep insight into how the subtle substitutions affect their OPV performances.